Zakat dan Kebijakan Fisikal Perspektif Ekonomi Islam: Tinjauan Kepustakaan - Novi Susanti (Social Science Academic, 2024)
This research aims to examine zakat and fiscal policy from an Islamic economic perspective. The study of zakat and fiscal policy addresses the law, function and purpose of zakat, as well as its application in Islamic economics. The method used in this research is a study of librarianship taken from a number of national journals with legal parameters, functions, and purposes of zakat, as well as its application in Islamic economics. The results of the study show that zakat and fiscal policy are important applied to realize social justice, economic well-being, fair distribution of wealth in accordance with the principles of Islamic economics.